2016
DOI: 10.1177/0021998316644847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sonication and clay content on the properties of unsaturated polyester/montmorillonite nanocomposites

Abstract: The aim of this work is to evaluate the effect of sonication and clay content on the crosslinking and curing characteristics and the final properties of unsaturated polyester/montmorillonite nanocomposites. The Cloisite 30B clay (1, 3 or 5 wt.%) was dispersed in the resin by mechanical stirring and sonication at different ultrasonic amplitudes (20% and 30%). Amplitude is one of the most important parameter when reproducing sonication results. An increase in viscosity with clay incorporation, at 20% amplitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…% of the used nanofillers may increase the viscosity of the epoxy, make it difficult to distribute HNC into epoxy, leading to an inadequate distribution of HNC, and offer opportunities to form the agglomeration and clusters which adversely affect the crashworthiness properties. Referring to Ho et al, 53 Azeez et al, 54 Islam et al, 55 Rafiq et al, 56 Fathy et al, 57 Romanzini et al, 58 and Bahari-Sambran et al, 59 the most beneficial effect is in general attained with a small wt. % of nanofillers, that is, less than 5 wt.…”
Section: Methodsmentioning
confidence: 97%
“…% of the used nanofillers may increase the viscosity of the epoxy, make it difficult to distribute HNC into epoxy, leading to an inadequate distribution of HNC, and offer opportunities to form the agglomeration and clusters which adversely affect the crashworthiness properties. Referring to Ho et al, 53 Azeez et al, 54 Islam et al, 55 Rafiq et al, 56 Fathy et al, 57 Romanzini et al, 58 and Bahari-Sambran et al, 59 the most beneficial effect is in general attained with a small wt. % of nanofillers, that is, less than 5 wt.…”
Section: Methodsmentioning
confidence: 97%
“…Since the organically modified montmorillonite (OMMT) was firstly introduced into Nylon‐6 matrix by Toyota research group, discovering that very small amounts of layered silicate loadings resulted in improvements of thermal and mechanical properties, OMMT‐based nanocomposites have attracted keen interest in academics and industry. Followed reports showed that mechanical properties, thermostability, flame retardancy, volumetric shrinkage, and the gas barrier effect could be greatly improved by the incorporation of OMMT nanoparticles. These improvements are attributed to the intercalated or exfoliated structure of clay in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used in extrusion processes to form fruit coating, in the packaging of juices, dairy products and in the production of bottles for beer and carbonated beverages. The polymeric matrices used for the incorporation of nanocomposite include polyamides, polyolefins, polystyrene, ethylene vinyl acetate, polyethylene, among others (Barbalho, 2018;Romanzini et al, 2017;Decker et al, 2015;Chaudhry et al, 2008).…”
Section: Introductionmentioning
confidence: 99%